PENERAPAN PRINSIP SYARIAH DALAM LAYANAN PERBANKAN DIGITAL DAN TEKNOLOGI FINANSIAL (FINTECH) DI BANK SYARIAH INDONESIA CABANG JEMBER - Ulum, Bachrul (JSE: Jurnal Sharia Economica, 2025)
Digital transformation in the banking sector has become a strategic necessity to address changing customer behavior, which increasingly prioritizes convenience, speed, and transaction security. Bank Syariah Indonesia (BSI), as the largest Islamic bank in Indonesia, responded to this trend by migrating its mobile banking services from BSI Mobile to a new platform called Beyond by BSI. This study aims to analyze the role of this migration in improving customer service quality, identify supporting and inhibiting factors for implementation, and evaluate its impact on customer satisfaction and loyalty. The research method used was a qualitative approach with in-depth interviews with customers and management, supported by secondary data from BSI's internal reports and publications from the Financial Services Authority (OJK). The results show that Beyond by BSI provides a better service experience through more comprehensive features, an intuitive interface design, and increased transaction security. However, challenges that emerged included user adaptation to system changes and the need to increase digital literacy among some customer segments. In conclusion, the Beyond by BSI migration contributed positively to improving customer service and satisfaction, while strengthening BSI's position in the competitive national digital banking industry.